Mechanically-flexible wafer-scale integrated-photonics fabrication platform - Milica Notaros; Thomas Dyer; Andres Garcia Coleto; Ashton Hattori; Kevin Fealey; Seth Kruger; Jelena Notaros (Scientific Reports, 2024)
Abstract The field of integrated photonics has advanced rapidly due to wafer-scale fabrication, with integrated-photonics platforms and fabrication processes being demonstrated at both infrared and visible wavelengths. However, these demonstrations have primarily focused on fabrication processes on silicon substrates that result in rigid photonic wafers and chips, which limit the potential application spaces. There are many application areas that would benefit from mechanically-flexible integrated-photonics wafers, such as wearable healthcare monitors and pliable displays. Although there have been demonstrations of mechanically-flexible photonics fabrication, they have been limited to fabrication processes on the individual device or chip scale, which limits scalability. In this paper, we propose, develop, and experimentally characterize the first 300-mm wafer-scale platform and fabrication process that results in mechanically-flexible photonic wafers and chips. First, we develop and describe the 300-mm wafer-scale CMOS-compatible flexible platform and fabrication process. Next, we experimentally demonstrate key optical functionality at visible wavelengths, including chip coupling, waveguide routing, and passive devices. Then, we perform a bend-durability study to characterize the mechanical flexibility of the photonic chips, demonstrating bending a single chip 2000 times down to a bend diameter of 0.5 inch with no degradation in the optical performance. Finally, we experimentally characterize polarization-rotation effects induced by bending the flexible photonic chips. This work will enable the field of integrated photonics to advance into new application areas that require flexible photonic chips.